2016
DOI: 10.1074/jbc.m115.708156
|View full text |Cite
|
Sign up to set email alerts
|

EVI1 Interferes with Myeloid Maturation via Transcriptional Repression of Cebpa, via Binding to Two Far Downstream Regulatory Elements

Abstract: One mechanism by which oncoproteins work is through perturbation of cellular maturation; understanding the mechanisms by which this occurs can lead to the development of targeted therapies. EVI1 is a zinc finger oncoprotein involved in the development of acute myeloid leukemia; previous work has shown it to interfere with the maturation of granulocytes from immature precursors. Here we investigate the mechanism by which that occurs, using an immortalized hematopoietic progenitor cell line, EML-C1, as a model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Interestingly, CEBPA expression in these subtypes of AML is often downregulated, and the direct binding of these oncoproteins to the enhancer could explain this effect. In fact, Perkins and colleagues 94 demonstrated that Evi1 binding to the murine 137 Kb enhancer is associated with a reduction of Cebpa expression in Evi1-expressing mouse myeloid leukemia lines. Potentially, the oncoproteins may alter active chromatin states at the enhancer(s), leading to inactivation of CEBPA.…”
Section: Hijacking Of the Cebpa Locus By Potential Oncoproteinsmentioning
confidence: 99%
“…Interestingly, CEBPA expression in these subtypes of AML is often downregulated, and the direct binding of these oncoproteins to the enhancer could explain this effect. In fact, Perkins and colleagues 94 demonstrated that Evi1 binding to the murine 137 Kb enhancer is associated with a reduction of Cebpa expression in Evi1-expressing mouse myeloid leukemia lines. Potentially, the oncoproteins may alter active chromatin states at the enhancer(s), leading to inactivation of CEBPA.…”
Section: Hijacking Of the Cebpa Locus By Potential Oncoproteinsmentioning
confidence: 99%
“…In fact, AML1‐ETO represses CEBPA transcription, indicating that GATA2 mutations arise on the fertile ground of CEBPA deficiency—due to either CEBPA mutation or downregulation (Figure , right panel). Another example for this correlation is AML with 3(q21;q26) aberrations, where the overexpression of EVI1 (MECOM) represses CEBPA , thus providing the basis for acquisition of GATA2 mutations. Additionally, somatic GATA2 mutations are either lost or acquired as the disease progresses .…”
Section: Resultsmentioning
confidence: 99%
“…To mimic the effects of rearrangements at 3q26 in AML, we created a tetracycline (Tet)-inducible allele of Evi1 (termed Evi1 TO ) in the mouse by inserting seven Tet operons within the first exon (Fig. 1a 15 ), allowing for the induction of all three isoforms of Evi1 8 , 9 . Evi1 TO/TO mice are viable and fertile without phenotype indicating that the allele functions normally in the uninduced state.…”
Section: Resultsmentioning
confidence: 99%
“… 22 , 23 ) and can modulate the transcription of target genes via binding in cis (e.g., refs. 15 , 24 ), we wished to determine if the myeloid skewing phenotype induced by EVI1 was dependent on its binding to DNA using two EVI1 mutants (Fig. 6a ): EVI1-R205N, which lacks DNA binding via ZF domain1 8 and EVI1-R769C, which lacks DNA binding via ZF2 25 .…”
Section: Resultsmentioning
confidence: 99%